Some solution of the fractional iterative integro-differential equations - Kilicman, Adem; Damag, F. H. M. (Institute for Mathematical Research, Universiti Putra Malaysia, 2018)
In this article, we focus to some classes of fractional iterative integro-differential equations. Firstly, we interested of the fractional iterative integro-differential equations including derivatives and establish the existence and uniqueness solutions by using the non-expansive operators theory and fixed point theorems. The second studies, we concern of the system iterative integro-differential equations and show existence and uniqueness solutions by using the theorem of Banach fixed point and Schaefer fixed point theorem. In this study, we consider Riemann-Liouville and Caputo differential operator, further provide example as an application.